2017
DOI: 10.1039/c7ra00824d
|View full text |Cite|
|
Sign up to set email alerts
|

Stable DNA-based reaction–diffusion patterns

Abstract: We demonstrate reaction-diffusion systems that generate stable patterns of DNA oligonucleotide concentrations within agarose gels, including linear and "hill" (i.e. increasing then decreasing) shapes in one and two dimensions. The reaction networks that produce these patterns are driven by enzyme-free DNA strand-displacement reactions, in which reactant DNA complexes continuously release and recapture target strands of DNA in the gel; a balance of these reactions produces stable patterns. The reactant complexe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 65 publications
1
35
0
Order By: Relevance
“…(1). For instance, recent advances in (bio)materials science are enabling material design and control at submicron and nano scales [66] through DNA circuits based on reaction-diffusion systems [67,68]. Working at such small scales, it is important to assess the potential quantitative and qualitative influence of external and internal noise in the relevant reaction-diffusion processes and systems.…”
Section: Discussionmentioning
confidence: 99%
“…(1). For instance, recent advances in (bio)materials science are enabling material design and control at submicron and nano scales [66] through DNA circuits based on reaction-diffusion systems [67,68]. Working at such small scales, it is important to assess the potential quantitative and qualitative influence of external and internal noise in the relevant reaction-diffusion processes and systems.…”
Section: Discussionmentioning
confidence: 99%
“…To address this need, recent work has begun to explore the feasibility of DNA-only reaction-diffusion patterns. 29,[34][35][36][37] Toehold-mediated DNA strand displacement has proved to be a convenient framework for implementing complex reaction sequences using synthetic DNA in well-mixed test tubes. 38,39 Using the principles of strand displacement, researchers have created sophisticated reaction networks that perform computation like neural networks, 40,41 diagnostic classifiers, 42 dynamic 3D nanostructures 43,44 and even approximate the dynamics of formal, mathematically specified chemical reaction networks (CRNs).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, Zenk et al. demonstrated the formation of stable 1‐dimensional DNA gradients in an agarose hydrogel medium by supplying reactants from liquid reservoirs at the edges of the gel [27] . Here, we construct attractor patterns using synthetic DNA strand displacement networks (Figure 1 a).…”
Section: Introductionmentioning
confidence: 98%
“…[12] Previously,Z enk et al demonstrated the formation of stable 1-dimensional DNAg radients in an agarose hydrogel medium by supplying reactants from liquid reservoirs at the edges of the gel. [27] Here,weconstruct attractor patterns using synthetic DNAs trand displacement networks ( Figure 1a). We show how such patterns form as designed and can recover their original shapes after perturbations.T oprecisely perturb patterns,w eu se UV light-triggered strand displacement reactions that degrade the patterned species (Figure 1b,c).…”
Section: Introductionmentioning
confidence: 99%